2005
DOI: 10.1155/asp.2005.1292
|View full text |Cite
|
Sign up to set email alerts
|

A Perceptual Model for Sinusoidal Audio Coding Based on Spectral Integration

Abstract: Psychoacoustical models have been used extensively within audio coding applications over the past decades. Recently, parametric coding techniques have been applied to general audio and this has created the need for a psychoacoustical model that is specifically suited for sinusoidal modelling of audio signals. In this paper, we present a new perceptual model that predicts masked thresholds for sinusoidal distortions. The model relies on signal detection theory and incorporates more recent insights about spectra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
77
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(78 citation statements)
references
References 37 publications
1
77
0
Order By: Relevance
“…Recently, it has been shown that significant improvements are gained by taking spectral integration into account [30], [31]. Using the masking model proposed in [30], [31], which was derived specifically for sinusoidal coding, the distortion D for a particular segment can be written as…”
Section: A Perceptual Distortion Measurementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been shown that significant improvements are gained by taking spectral integration into account [30], [31]. Using the masking model proposed in [30], [31], which was derived specifically for sinusoidal coding, the distortion D for a particular segment can be written as…”
Section: A Perceptual Distortion Measurementioning
confidence: 99%
“…A recently published psychoacoustic masking model for audio coding has been shown to form a distortion measure [30], [31], and this distortion measure has been applied successfully to the sinusoidal estimation problem in [15], [23], [32], [33]. Based on this we define the perceptual frequency estimation problem and its optimal solution.…”
Section: Introductionmentioning
confidence: 99%
“…A mathematical expression approximating the threshold in quiet can be found in [1]. For the auditory filter bank the same gammatone-based approach as in [7] is used. In total 64 filters are used where the center frequencies are linearly spaced on an ERB-scale between 0 and Hz, where denotes the sample rate.…”
Section: A Auditory Modelmentioning
confidence: 99%
“…Van de Par et al introduced a perceptual distortion measure, which we will refer to as the Par-model, including spectral integration [7]. That is, the detectability of a specific frequency component is also determined by off-frequency auditory filters.…”
mentioning
confidence: 99%
See 1 more Smart Citation